การใช้การประเมินความต้องการจำเป็นในการออกแบบการพัฒนาบุคลากร ด้านการประเมินโครงการในสถานศึกษาอาชีวศึกษา - โตบัว สุนทรา; เข็มทอง พนิต; ธรรมกิตติภพ วรัทยา (Journal of Research and Curriculum Development, 2019)
The objectives of this study were to analyze needs assessment for vocational Personnel development in project evaluation design and study the results. Research and Development design was employed in 2 phase; phase 1 analyse completely need assessment include 3 stage: stage 1 needs identification , stage 2 needs analysis, and stage 3 needs solution. The target group was 100 personnel in vocational education institutions responsible for the projects from 5 regions. Data were collected by interview and questionnaire. Analyze data by modified priority needs index and matrix analysis, stage 2 design and study the results of personnel development in vocational education institutions based on the needs assessment. The personnel development model was a training course on project evaluation and logical models were used in curriculum design. The curriculum development include 3 stage: stage 1 create a training course content consists of 5 units; 1) concepts of project evaluation 2) indicators and criteria for evaluation 3) tools and data collection 4) data analysis 5) evaluation report writing. The training sessions take 7 hours/ day for 2 days, a total of 14 hours. The content validity confirmed by 3 experts had an IOC 0.67 - 1.00 and seminars to criticize the training course before implementation. Research design using pre- experimental: one-group pretest-posttest design. The target group was 70 participants in vocational institutes. Data collection tools were: knowledge test, evaluation form and questionnaire. The results of the course training were met the output indicators; the participants had more knowledge, all projects design quality were good and 80% of participants had the high to highest level of satisfaction.